A SYNTACTICAL ANALYSIS ON SENTENCE PATTERNS USED IN BARACK OBAMA SPEECH - Manossoh, Jeniver R.; Samola, Nurmin; Olii, Sanerita T. (English Education Department, 2022)
This study focuses on 9 basic sentence patterns that used in Barack Obama speech which he delivered when visited Universitas Indonesia Jakarta The aim of the study is to find out how many sentence patterns that used in Barack Obama Speech This study used qualitative research which the researcher analyzed through the script The results of the study showed that there were 8 sentence patterns in the speech as follows they were pattern 1 9 sentences pattern 2 2 sentences pattern 3 26 sentences pattern 4 1 sentence pattern 6 20 sentences pattern 7 103 sentences pattern 8 1 sentence pattern 9 2 sentences Based on the result it can be concluded that the pattern 7 were most dominant of the other pattern then there was 1 pattern was not found pattern 5 In this research there were various kinds of sentences pattern in 1 speech that can be used to help you improve writing skill for English learners especially for the future researchers< p>